Knowledge, attitude and practice of evidence-based medicine among primary care practitioners in Malaysia: a cross-sectional study - Mohd Noor Norhayati; Mat Nawi Zanaridah; Zakaria Rosnani (BMJ Open)
Objectives To determine the level of knowledge and practice of evidence-based medicine (EBM) and the attitudes towards it and to identify the factors associated with its practice among primary care practitioners in Selangor, Malaysia.Setting This cross-sectional study was conducted in randomly selected health clinics in Selangor. Data were collected from primary care physicians using self-administered questionnaires on knowledge, practice and attitudes regarding EBM.Participants The study included 225 respondents working in either government or private clinics. It excluded house officers and those working in public and private universities or who were retired from practice.Results A total of 32.9% had a high level of EBM knowledge, 12% had a positive attitude towards EBM and 0.4% had a good level of its practice. The factors significantly associated with EBM practice were ethnicity, attitude, length of work experience as a primary care practitioner and quick access to online reference applications on mobile phones.Conclusions Although many physicians have suboptimal knowledge of EBM and low levels of practising it, majority of them have a neutral attitude towards EBM practice. Extensive experience as a primary care practitioner, quick access to online references on a mobile phone and good attitude towards EBM were associated with its practice.